THE SIGNIFICANCE OF MICROORGANISMS IN HUMAN LIFE AND THE METHODOLOGY OF TEACHING THE SUBJECT (Web of Teachers: Inderscience Research, 2026)
The article examines the role of microorganisms in nature and their significance in human life, particularly within the pharmaceutical industry. Central focus is given to the morphological structure of the Penicillium genus, the discovery of penicillin, and its biosynthesis process. Furthermore, the paper analyzes the challenge of antibiotic resistance and the future potential of modern genetic technologies such as CRISPR/Cas9. In the methodological section, the effectiveness of interactive teaching strategies - including “Biosynthesis Logic”, the “Pharmaceutical Pyramid”, and the “Microbiological Basket” is substantiated for teaching microbiology in higher education.